How to improve health literacy to reduce short- and long-term consequences of maternal obesity?. (2nd September 2019) - Arabin, Birgit; Timmesfeld, Nina; Noever, Kathrin; Behnam, Susann; Ellermann, Christin; Jenny, Mirjam A.
Abstract: Aim: To demonstrate the global challenge of maternal obesity and to propose models to increase awareness and health literacy. Methods: The regional perinatal data base and the international literature were reviewed to demonstrate the rising rates of maternal overweight and obesity causing major public health problems in low and high-resourced countries. A preliminary systematic review analyzing interventions in maternal obesity and a fact box based on a recent Cochrane review on dietary interventions were performed. Results: Between 2000 and 2015, the regional rates of maternal overweight and obesity have significantly increased, and the rate of morbid maternal obesity has even doubled. Pregnant women were insufficiently informed about the health risks and international recommendations for weight gain associated with pre-pregnancy body mass index. Scientific publications and guidelines of professional boards have not yet interrupted the vicious cycle of transgenerational transfer of associated health risks for the offspring. For the first time we propose a fact box to translate the results from a Cochrane review about dietary interventions into a transparent information for health care providers and patients which could help to improve awareness. Conclusions: Improving health literacy and translating clinical science into models which are understandable by policy makers, health care providers and parents is a challenge mainly if health risks are modifiable during gestation and could prevent the increasing burden of obesity for future societies.